2000
DOI: 10.1053/jvet.2000.5601
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bone Healing by Demineralized Bone Matrix and Autogenous Cancellous Bone in Horses

Abstract: Particles of 2 to 4 mm DBM should not be used as an aid to fracture repair because particles of this size interfere with normal mineralization. However, our model of nonunion fracture healing may be useful in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 33 publications
3
21
0
3
Order By: Relevance
“…Better results with autogenous bone graft are credited to its lack of immunogenicity, minimum inflammatory reaction and easy revascularization, great quantity of viable cells and high potential of osteoconduction and osteoinduction (Piattelli et al, 1996;Rabie and Lie Ken Jie, 1996;Kawcak et al, 2000;Rabie and Chay, 2000). The present results showed favorable influence on the use of autogenous graft, confirming the superiority of autogenous grafts as reconstructive materials.…”
Section: Discussionsupporting
confidence: 73%
“…Better results with autogenous bone graft are credited to its lack of immunogenicity, minimum inflammatory reaction and easy revascularization, great quantity of viable cells and high potential of osteoconduction and osteoinduction (Piattelli et al, 1996;Rabie and Lie Ken Jie, 1996;Kawcak et al, 2000;Rabie and Chay, 2000). The present results showed favorable influence on the use of autogenous graft, confirming the superiority of autogenous grafts as reconstructive materials.…”
Section: Discussionsupporting
confidence: 73%
“…By using an appropriate matrix, it may be possible to construct a single unit that is capable of repairing both the chondral and subchondral aspects of the defect (10). The BMG used in this study was reported to be a suitable scaffold supporting the growth of osteochondral tissue (11). The widely available natural polymer, fibrin, has been reported to be an ideal cell carrier (12).…”
Section: Discussionmentioning
confidence: 92%
“…In these cases, species-specific DBM is required. 42,46 Commonly, for osteoinductivity assays, the DBM is resident in the animal for at least 28 days. 45 After explantation, histomorphometry is performed on stained, embedded, decalcified sections.…”
Section: Demineralized Bone Matrixmentioning
confidence: 99%